(untitled) (Al-Mukhtar Journal of Basic Sciences, 2026)
Fuzzy ordinary differential equations (FODEs) extend classical ordinary differential equations (ODEs) to systems characterized by uncertainty and imprecision, often modeled using fuzzy set theory. In this work we use homotopy analysis method (HAM) to solve FODEs, and show how HAM works. (HAM) is an easy and effective method to solve linear and nonlinear ordinary differential equations. HAM does not need small parameters or special tricks like linearization. Instead, it builds a smooth path from a simple starting guess to the real solution by using a special parameter and function.